2022-RA-1268-ESGO Surgery after primary chemo/radiation in locally advanced vulvar cancer: analysis of surgical outcomes and survival. (20th October 2022) - Fragomeni, Simona Maria; Federico, Alex; Lancellotta, Valentina; Tagliaferri, Luca; Bove, Sonia; Caretto, Anna Amelia; Gentileschi, Stefano; Corrado, Giacomo; Scambia, Giovanni; Garganese, Giorgia
Abstract : Introduction/Background: More than 30% of vulvar cancer new cases are locally advanced (LAVC). The treatment of LAVC consists of primary radiotherapy, +/- chemotherapy – (CT)RT. Surgery is scheduled after neoadjuvant treatment or added to exclusive (CT)RT to debulk residual disease. Our aim was to assess survival and surgical complications in this setting. Methodology: Patients with squamous LAVC submitted to (CT)RT and surgery at our Institution between January 2016 and December 2021 were retrospectively evaluated. Results: 51 patients were submitted to primary (CT)RT: 40 (78, 4%) had a clinical response (complete in 18 and partial in 22 cases), 1 (2%) stable and 10 (19.6%) progression disease. Overall, 19/51 (37.2%) patients underwent surgery.Regarding baseline nodal involvement of surgically treated patients, the work up showed 6 (31, 6%) clinically negative, 3 (15, 8%) clinically positive inguinal nodes and 10 (52, 6%) pelvic nodal disease. Surgeries were classified as radical [vulvar and/or inguinal surgery, n=5 (26.3%)] and ultra-radical [requiring plastic reconstruction and/or pelvic surgery (visceral or lymph-nodal), n=14 (73.7%)]. Overall, 17 patients (89, 4%) experienced a post operative complication with a Clavien-Dindo grade ≤2 in 58, 8% of cases (17, 6% after radical and 41, 2% after ultra-radical surgery) ( Table 1 ).Five (26.3%) patients showed pathological complete response (pCR), while 14 (73.7%) had residual tumor [7 (36.8%) vulvar-site, 1 (5.3%) LN-site and both-sites in 6 (31.6%) cases].The 3-years disease-free survival was 100% in case of pCR and 30.8% for residual tumor, (p=0.036) ( Figure 1 ). Conclusion: A high rate of clinical responses (complete/partial) to (CT)RT was registered. Post-operative complications resulted acceptable compared to literature data. pCR is associated with excellent survival also in these tumors as demonstrated in other neoplasms. The multidisciplinary approach is crucial to complete the combined treatment planned [(CT)RT+/- surgery]. In the future, predictive models could allow to select patients on the basis of their foreseen response.